World-systems Foundations of Supradisciplinary Synthesis: Program Outlines for Studying the Dynamics of Societies in the Post-Soviet Space - A. A. Izgarskaya (Дискурс, 2022)
Introduction. The study of processes in societies in the post-Soviet space exceeds the scope of any single scientific discipline. All the existing attempts at interdisciplinary synthesis do not allow to overcome the fragmentation of scientific knowledge. The article describes the structure of the foundations of the supradisciplinary synthesis based on the ideas of  I. Wallerstein. An analysis of the concept of Eurasianism (which, in the author's opinion, is the most influential interdisciplinary direction in modern domestic social science that studies processes in the post-Soviet space) was carried out with the aim of subsequent synthesis with the world-systems approach.Methodology and sources. The foundations of the supradisciplinary synthesis are the concept of the world-systems approach by I. Wallerstein, the characteristics of macro-, meso-, microsocietal levels by J. Turner, and the idea of four spheres of socio-historical existence by N. S. Rozov (biotechnosphere, psychosphere, cultural sphere, sociosphere).Results and discussion. The resulting structure of the supradisciplinary synthesis is a tool that will allow: to systematize the existing developments in the field of the world-systems approach; to discover existing gaps and fill them by synthesis with directions that do not contradict the world-systems approach; to carry out a critical analysis of theories of competing paradigms with world-systems analysis by comparing their empirical areas; systematically expand the empirical field and develop the world-systems theory. The tradition laid down by the historiosophy of Eurasianism is a culture-centered direction with additional accents in the biotechnosphere, sociosphere and psychosphere. At the present stage this contributes to its development as an interdisciplinary field of research. In Eurasianism, there is no ontology of the world as a system that includes societies in the structures of intersocietal ties and acts as a “containment environment” for their development. The Eurasian concept has an antisystemic ideological basis, and for this reason it is difficult to explain on its basis the desire of the post-Soviet states to integrate into the world system, their mutual competition and military conflicts.Conclusion. The supradisciplinary synthesis with world-systems analysis will allow Eurasianism to overcome the existing gaps in ontology and strengthen the explanatory potential. The empirical baggage accumulated by Eurasianism will receive a world-systems interpretation of processes in the post-Soviet space, which will serve to expand the empirical field of the world-systems approach.